IDENTIFIKASI POTENSI LONGSOR MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KECAMATAN SALEM KABUPATEN BREBES - Isbakhul Lail; Bakti Wisnu Widjajani; Kemal Wijaya (Plumula : Berkala Ilmiah Agroteknologi, 2019)
Based on BNPB, victims of landslides on February 22, 2018 a total of 11 people died and 7 people were missing. Landslides occur due to steep slope and geological material form in the form of marl so that it can be used as a field of sliding ground movements. Data processing Geological maps and land cover in the form of shapefiles were cliped in the study area. Determination of the level of vulnerability of landslides in the study area is based on the estimation model of landslide prone areas by the Directorate of Volcanology and Geological Disaster Mitigation / DVMBG (2004). Score = (30% x rainfall class factor) + (20% x geology) + (20 % x class Erodibility factor) + (15% x land use) + (15% x slope class factor). Based on the research carried out, the highest landslide prone areas were in the village of Ciputih with an area of 943 Ha and wanoja with an area of 684 Ha, the area under control was landslide in the village of the balance area of 893 Ha and wanoja covering an area of 708.37 Ha. While the low landslide area is in Salem village covering an area of 1193 Ha. The most influential factors were slope 46 % and erodibility 35 %. Both of them potential landslide happen.